Fundamental studies for the proton polarization technique in neutron protein crystallography. (1st October 2013) - Tanaka, Ichiro; Kusaka, Katsuhiro; Chatake, Toshiyuki; Niimura, Nobuo
<x xml:space="preserve">Abstract</x> The isotope effect in conventional neutron protein crystallography (NPC) can be eliminated by the proton polarization technique (ppt). Furthermore, the ppt can improve detection sensitivity of hydrogen (relative neutron scattering length of hydrogen) by approximately eight times in comparison with conventional NPC. Several technical difficulties, however, should be overcome in order to perform the ppt. In this paper, two fundamental studies to realise ppt are presented: preliminary trials using high‐pressure flash freezing has shown the advantage of making bulk water amorphous without destroying the single crystal; and X‐ray diffraction and liquid‐chromatography/mass‐spectrometry analyses of standard proteins after introducing radical molecules into protein crystals have shown that radical molecules could be distributed non‐specifically around proteins, which is essential for better proton polarization.